2013
DOI: 10.3389/fnins.2013.00164
|View full text |Cite
|
Sign up to set email alerts
|

Novel progesterone receptors: neural localization and possible functions

Abstract: Progesterone (P4) regulates a wide range of neural functions and likely acts through multiple receptors. Over the past 30 years, most studies investigating neural effects of P4 focused on genomic and non-genomic actions of the classical progestin receptor (PGR). More recently the focus has widened to include two groups of non-classical P4 signaling molecules. Members of the Class II progestin and adipoQ receptor (PAQR) family are called membrane progestin receptors (mPRs) and include: mPRα (PAQR7), mPRβ (PAQR8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 98 publications
(153 reference statements)
0
65
1
5
Order By: Relevance
“…The Role of PGRMC1 in Modulating Insulin Secretion in Pancreatic ␤ Cells-As mentioned, PGRMC1 belongs to the MAPR family (39) and binds progesterone with high affinity in mammalian cells. It also has the ability to bind other molecules, including testosterone, glucocorticoids, heme, and cholesterol metabolites (32,33).…”
Section: Affinity Purification and Mass Spectrometry Revealed Potentimentioning
confidence: 99%
“…The Role of PGRMC1 in Modulating Insulin Secretion in Pancreatic ␤ Cells-As mentioned, PGRMC1 belongs to the MAPR family (39) and binds progesterone with high affinity in mammalian cells. It also has the ability to bind other molecules, including testosterone, glucocorticoids, heme, and cholesterol metabolites (32,33).…”
Section: Affinity Purification and Mass Spectrometry Revealed Potentimentioning
confidence: 99%
“…IRE1 inhibition also upregulates the expression level of PGRMC2, a potential downstream eff ector of FOXM1 transcription factor, which plays important roles in the tumorigenesis and tumor metastasis in multiple human carcinomas as tumor suppressor and migration inhibitor (Wendler and Wehling 2013;Petersen et al 2013;Ye et al 2015). Another estrogen-responsive protein, TRIM16, which inhibits hepatocellular carcinoma cell migration and invasion by suppression of ZEB2 expression as well as suppresses cancer cell viability by involving interaction and stabilization of TDP43 with consequent eff ects on E2F1 and pRb proteins (Kim et al 2016), is also up-regulated in glioma cells without IRE1 signaling enzyme function.…”
Section: Discussionmentioning
confidence: 99%
“…Pedram et al (2006) have shown that in the mitochondria of MCF-7 breast cancer cells and endothelial cells there are high-affi nity estrogen receptors, which impact mitochondrial functions and control the survival of the tumor cells. PGRMC2 (progesterone receptor membrane component 2) also known as steroid receptor protein DG6 and progesterone membrane binding protein (PMBP), is a member of non-classical progesterone signaling molecules (membrane progestin receptors) and a potential downstream eff ector of FOXM1 transcription factor, which plays important roles in tumorigenesis and tumor metastasis in multiple human carcinomas as tumor suppressor, migration inhibitor, and regulator of cytochrome P450 proteins (Petersen et al 2013;Wendler and Wehling 2013;Ye et al 2015).…”
mentioning
confidence: 99%
“…The mPRs were first discovered and characterized in fish ovaries (Zhu et al, 2003a), and five isoforms (mPRα, mPRβ, mPRγ, mPRδ, mPRε) were subsequently identified in humans and other vertebrates (Zhu et al, 2003b;Thomas et al, 2012;Peterson et al, 2013). Both nPRs and mPRs are highly expressed in testis (Ikeuchi et al, 2002;Hanna et al, 2009) and brain (Thomas et al, 2012;Peterson et al, 2013), but the functions mediated by them are still unclear. In Japanese eel, progestin receptor 1 (pgr1) is expressed in testis germ cells, Sertoli cells, and testis interstitial cells, whereas progestin receptor 2 (pgr2) mRNA has been detected only in testis germ cells .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has been obtained that steroid hormones, thyroid hormones, and vitamin D, similarly to water soluble signalling molecules, exert this rapid cell surface-initiated hormone action through binding to membrane receptors, which lead to the activation of intracellular second messenger pathways (Revelli et al, 1998;Watson et al, 1999;Falkenstein et al, 2000;Norman et al, 2004). The mPRs were first discovered and characterized in fish ovaries (Zhu et al, 2003a), and five isoforms (mPRα, mPRβ, mPRγ, mPRδ, mPRε) were subsequently identified in humans and other vertebrates (Zhu et al, 2003b;Thomas et al, 2012;Peterson et al, 2013). Both nPRs and mPRs are highly expressed in testis (Ikeuchi et al, 2002;Hanna et al, 2009) and brain (Thomas et al, 2012;Peterson et al, 2013), but the functions mediated by them are still unclear.…”
Section: Introductionmentioning
confidence: 99%